2019
DOI: 10.1159/000502489
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models Reflecting Chronic Obstructive Pulmonary Disease and Related Respiratory Disorders: Translating Pre-Clinical Data into Clinical Relevance

Abstract: Chronic obstructive pulmonary disease (COPD) affects the lives of an ever-growing number of people worldwide. The lack of understanding surrounding the pathophysiology of the disease and its progression has led to COPD becoming the third leading cause of death worldwide. COPD is incurable, with current treatments only addressing associated symptoms and sometimes slowing its progression, thus highlighting the need to develop novel treatments. However, this has been limited by the lack of experimental standardiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 325 publications
(318 reference statements)
1
75
0
1
Order By: Relevance
“…Many studies found elevated MMPs concentration and increased elastin degradation in chronic obstructive pulmonary diseases [21][22][23]. Neutrophil elastase or matrix metalloproteinases (MMPs) were held culprit [24]. But it appears that the protease secreted by various bacteria had never been taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies found elevated MMPs concentration and increased elastin degradation in chronic obstructive pulmonary diseases [21][22][23]. Neutrophil elastase or matrix metalloproteinases (MMPs) were held culprit [24]. But it appears that the protease secreted by various bacteria had never been taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used a 21-day intratracheally bleomycin-challenged murine model to confirm TH5487 efficacy in vivo. This model reproduces several phenotypic features of human IPF, including peripheral alveolar septal thickening and acute cytokine production resolving in fibrosis (19,20).…”
Section: Introductionmentioning
confidence: 89%
“…Subsequent analysis of functions may use epithelial cell models such as the air-liquid interface, in vitro airway epithelial model that has been adapted to studying viral infection and the changes it induced in the airway (Yan et al, 2016;Boda et al, 2018;Tan et al, 2018a). Animal-based diseased models have also been developed to identify systemic mechanisms of acute exacerbation (Shin, 2016;Gubernatorova et al, 2019;Tanner and Single, 2019). Furthermore, the humanized mouse model that possess human immune cells may also serves to unravel the immune profile of a viral infection in healthy and diseased condition (Ito et al, 2019;Li and Di Santo, 2019).…”
Section: Clinical Significance Of Identifying Additional Mechanisms Omentioning
confidence: 99%